2019
DOI: 10.7150/ijbs.31794
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Transporter Regulates Adipogenic Differentiation of Human Adipose-Derived Stem Cells through Affecting Wnt/β-catenin Signaling Pathway

Abstract: Increased adipocytes are associated with obesity and many human disorders including cancers. To further understand the molecular mechanisms of adipogenesis, transcriptome sequencing was performed to find genes involved in the adipogenic differentiation of human adipose-derived stem cells (hASCs). The mRNA of taurine transporter (TauT, also known as SLC6A6) was found significantly upregulated in hASCs undergoing differentiation. TauT expression was also markedly increased in fat tissues from obese mice induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The cultured cells and the human tissues were lysed with the appropriate amount of RIPA lysis buffer (Beyotime, Shanghai, China) containing 1 ×protease inhibitor mixture (Roche) and PMSF (Beyotime, Shanghai, China). The proteins in the supernatants were subjected to SDS-PAGE and immunoblotting as described previously ( Hou et al, 2019 ). The antibodies used were as follows: anti-PARP (Cell Signaling Technology), GSDME (Abcam), USP47 (Santa Cruz), GAPDH (Abgent Biotechnology), β-actin (Santa Cruz), α-Tubulin (Santa Cruz), Flag (Medical and Biological Laboratories), Myc (Medical and Biological Laboratories), Ub (Santa Cruz), Bax (Santa Cruz).…”
Section: Methodsmentioning
confidence: 99%
“…The cultured cells and the human tissues were lysed with the appropriate amount of RIPA lysis buffer (Beyotime, Shanghai, China) containing 1 ×protease inhibitor mixture (Roche) and PMSF (Beyotime, Shanghai, China). The proteins in the supernatants were subjected to SDS-PAGE and immunoblotting as described previously ( Hou et al, 2019 ). The antibodies used were as follows: anti-PARP (Cell Signaling Technology), GSDME (Abcam), USP47 (Santa Cruz), GAPDH (Abgent Biotechnology), β-actin (Santa Cruz), α-Tubulin (Santa Cruz), Flag (Medical and Biological Laboratories), Myc (Medical and Biological Laboratories), Ub (Santa Cruz), Bax (Santa Cruz).…”
Section: Methodsmentioning
confidence: 99%
“…For Trp, tryptophan metabolite 5-hydroxytryptamine (serotonin) can regulate white and brown adipose tissue function, including adaptive thermogenesis in mice [81]. Tau effectively inhibits adipocyte formation in a human adiposederived stem cell model, whereas TauT substrates hypotaurine and β-alanine promote adipogenesis [82]. Moreover, long-term Tau supplementation in mildly obese mice can inhibit adipogenesis in muscle and white adipose tissue, but not brown adipose tissue [83].…”
Section: Associations Among Gene and Protein Expression Amino Acid Lmentioning
confidence: 99%
“…Measurements of amino acid levels in placental chorionic villous fraction and plasma were conducted as previously described [82]. Instead of the iTRAQ Reagent Kit used in the publication, the amino acid levels were measured with the aTRAQ Reagent Kit 200 Assay (ABSciex, Foster City, USA) in combination with liquid chromatography-tandem mass spectrometry (LC-MS/MS).…”
Section: Amino Acid Analysismentioning
confidence: 99%
“…In this manner, it was proved that impaired hASCs differentiation accompanied by eliminated TauT transporter activity was recovered by hypotaurine and β-alanine through impeding β-catenin transcriptional transactivation. The results proposed that taurine transport can act as a new therapeutic strategy against obesity ( 89 ). Additional evidence supporting the functional importance of TauT transporter in diabetes, emerged through the phenotype of TauT transporter deficient animal models, in which researchers observed that characteristics of TauT transporter null animals comprised mesangial cell expansion, glomerular basement thickening, nodular sclerosis with expansion of the glomerulus beyond Bowman's capsule, and juxtaglomerular tuft sclerosis ( 90 ).…”
Section: Regulation Of Taut Transportermentioning
confidence: 99%